Cannabis treatment outcomes among legally coerced and non-coerced adults - Copeland Jan; Maxwell Jane C (BMC Public Health, 2007)
Abstract Background Treatment seeking for cannabis dependence in general, and particularly the number of criminal justice referrals to cannabis treatment, has increased over the past decade. This study aims to compare the characteristics, psychosocial functioning and treatment outcome of those legally coerced into cannabis treatment compared to those entering treatment without legal coercion. Methods This study is a retrospective audit of the administrative clinical records of 27,198 adults presenting to public Texas treatment programs with cannabis as their primary drug problem between 2000 and 2005. Results Of the 69% legally coerced into treatment, there was less psychological distress and greater likelihood of having completed treatment compared with non-coerced clients. Participants who were legally coerced into treatment were also more likely to have received less intensive forms of treatment and to have not used cannabis in the month prior to 90-day post-treatment follow-up. Conclusion More public health information is needed on cannabis dependence and increased availability of subsidised early and brief interventions in a variety of primary health care settings would reduce the late presentations of the more severely impaired voluntary clients. The limitations of this dataset are discussed.